Online database website usability & satisfaction / Mohd Firdaus Mohd Helmi...[et al.] - Mohd Helmi, Mohd Firdaus; Selamat, Nordibradini; Shari, Sharunizam (Universiti Teknologi MARA, Kedah, 2017)
Websites have long become important channels for advertising, sales and service support; and also serve as the platform for information exchange via intranet and extranet. Although websites provide several benefits to the organization, websites need to be usable in order to fulfil the user satisfaction. Besides that, there are growing concerns on how the websites are been developed and the degree of quality delivered. Supposedly, websites should reflect the need of the users, but sadly they have always been by technology and business objectives or organization structure rather than by user need. Therefore, this study is conducted to examine the level of usability and satisfaction and investigate the relationship between website usability and satisfaction of Emerald Online Database website. Usability refers to how easy the website is for every person to use, and incorporate design layout patterns that may be learned by users who then may explore the site and gain value from its content. Meanwhile, website satisfaction is the user's cognitive judgement that occurs after the website visit. It was discovered that, the level of usability and satisfaction of Emerald Online Database website is slightly above average. This study also found the usability has a significant and strong relationship with satisfaction. It can be concluded that usability aspects of the website play important roles in determining the level of satisfaction, and it should be given attention by website developer and administrator. This study also provides empirical evidence on the relationship between website usability and website satisfaction in the context of online database website.